Lattice gas study of the kinetics of the NO-CO catalytic reaction on Pd nanoclusters - Bustos Giunta, Victor Angel (2003)
The kinetics of the NO-CO reaction on Pd nanoclusters is studied through a lattice-gas model and Monte Carlo simulation. Pd nanoclusters with three typical sizes: 2.8 nm, 6.9 nm and 15.6 nm, are considered. These nanoclusters have been epitaxially grown on MgO(100) and tested for the NO-CO reaction in previous experimental work [ref. 9-11: C. H. F. Peden, D. W. Goodman, D. S. Blair, P. J. Berlowitz, G. B. Fisher and S. H. Oh, J. Phys. Chem., 1988, 92, 1563; C. Duriez, C. R. Henry and C. Chapon, Surf. Sci., 1991, 253, 190; L. Piccolo and C. R. Henry, Appl. Surf. Sci., 2000, 162-163, 670], thus providing the motivation for the present study. According to their size, the nanoclusters present different proportions of Pd(100) and Pd(111) facets. The effects of CO and NO desorption are found to be of fundamental importance for the behavior of the system. In all cases the medium size particles are found to be the most active. At low temperature, where NO desorption can be neglected (since the activation energy for desorption of NO on Pd is about 5 kcal mol-1 greater than that for the desorption of CO), the largest particles are revealed as the less active, while at high temperature, where both NO and CO desorption take place, the smallest particles are found to be the less active. These results are in concordance with the experimentally observed behavior.